A Review on Analysis of Self Supported Steel Chimney with The Effect Due to Flue Dust Opening and Geometrical Parameter - Khan, Sahil; Bandewar, Deepak (International Journal of Scientific Research in Civil Engineering, 2021)
A large portion of the mechanical steel smokestacks are tall designs with round cross-areas. Such thin, softly damped structures are inclined to wind-left vibration. Calculation of a self-supporting steel fireplace assumes a significant part in its underlying conduct under sidelong unique stacking. This is on the grounds that calculation is essentially answerable for the solidness boundaries of the smokestack. In any case, essential elements of modern self-supporting steel smokestack, like tallness, width at exit, and so forth, are for the most part gotten from the related natural conditions. In this study we are presenting review of literatures related to structural analysis and design of tall structures and chimneys using analysis tool.